2022
DOI: 10.3390/polym14163295
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Etherification of ortho-Phosphoric Acid for the Synthesis of Polyurethane Ionomer Films

Abstract: The etherification reaction of ortho-phosphoric acid (OPA) with polyoxypropylene glycol in the presence of tertiary amines was studied. The reaction conditions promoting the catalytic activity of triethanolamine (TEOA) and triethylamine (TEA) in the low-temperature etherification of OPA were established. The catalytic activity of TEOA and TEA in the etherification reaction of phosphoric acid is explained by the hydrophobic-hydrophilic interactions of TEA with PPG, leading, as a result of collective interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…After TEOA is fully involved in the etherification reaction, excess OPA does not react with the terminal hydroxyl groups of AEPA-PEG or the remaining amount of PEG. In our previous studies [58], it was experimentally shown that the rate constant of the OPA etherification reaction with triethanolamine exceeds the rate constant of the OPA etherification reaction with polyoxypropylene glycol.…”
Section: Study Of the Opa Etherificationmentioning
confidence: 92%
See 2 more Smart Citations
“…After TEOA is fully involved in the etherification reaction, excess OPA does not react with the terminal hydroxyl groups of AEPA-PEG or the remaining amount of PEG. In our previous studies [58], it was experimentally shown that the rate constant of the OPA etherification reaction with triethanolamine exceeds the rate constant of the OPA etherification reaction with polyoxypropylene glycol.…”
Section: Study Of the Opa Etherificationmentioning
confidence: 92%
“…In [58], the role of associative interactions of tertiary amines and PPG in the catalytically activated low-temperature etherification of OPA was discovered and proven. According to our research [59], the use of PEG instead of PPG also makes it possible to synthesize the corresponding aminoethers of ortho-phosphoric acid (AEPA-PEG).…”
Section: Study Of the Opa Etherificationmentioning
confidence: 99%
See 1 more Smart Citation